Vienna, Schwarzspanierhof - Czoernig-Gobanz, Herta, 1886-1970 (artist):::Creator:::::::::::: (2020)
Hand-colored etching of the Schwarzspanierhof in Vienna, location of Beethoven's last dwelling before it was demolished in 1903.